Specific features of the structure of a technical and tactical arsenal of Non-Olympic single combats of an impact type and a way of its improvement - Volodymyr Ashanin; Andriy Litvinenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: identify key differences in technical operations and tactical combat potential ways to implement popular athletes in combat shock type, applying for entry into the Olympic Games. Material and Methods: distinctions of sports technique and tactics in duels in karate, taekwondo, kickboxing and Thai boxing were estimated by the expert group. The arsenal of technical and tactical actions of sportsmen was analyzed at competitions of various levels. Results: essential distinctions in competitive exercises, estimated criteria of refereeing, the structure and the arsenal of the applied sports technique and tactics are revealed in chosen for the research types of impact single combats. Conclusions: essential differences in the technical - tactical arsenal of the studied types of impact single combats which are shown in the topography of zones allowed for drawing, the structure of attacking and protective actions, and also tactical stylistics of carrying out duels.